Fossil reefs reveal temporally distinct late holocene lagoonal reef shutdown episodes at Kiritimati island, Central Pacific - Ryan, E. J. (2022)
An extremely rare example of well-preserved emergent Holocene fossil reefs exists at Kiritimati Island, central Pacific. Fossil reefs are rich geological archives of paleoenvironmental change. The first paleoecological surveys of two fossil reefs are presented, revealing high coral cover (40–50%) and low diversity (6 genera). Fossil coral ages suggest reefs exhibited disparity in the timing of reef development (4,113 and 1,915 cal yBP) and ecological surveys show different coral compositions (Acropora or Porites dominant), between reefs. Results constrain two discrete episodes of reef shutdown (at 2,905 and 1,705 cal yBP) as lagoonal reefs thrived, and subsequently died off, through the late Holocene. Shifts in physio-chemical conditions associated with reduced lagoon flushing following storm-driven changes in atoll rim morphology are argued as the driver for the staged reef die-off. The findings have implications for interpreting past and future eco-morphological change on atolls, given projected increases in storminess with climate change.